Law Enforcement of Corruption Crimes in Geothermal Mining Sector in Indonesia to Realize the Value of Justice - Sindi Susanti; Maman Nurohman; Suwari Akhmaddhian (Unifikasi: Jurnal Ilmu Hukum, 2026)
In 2026, Indonesia recorded a low corruption perception index score of 38 and ranked 109th out of 180 countries. This condition emphasizes the crucial importance of law enforcement in strategic sectors such as renewable energy and mining. Purpose: This research aimed to analyze the regulation and implementation of law on corruption in Indonesia geothermal mining sector, with a focus on Decision Number 60/Pid.Sus-TPK/2023/PN.Jkt.Pst. Methods: A normative juridical method was used through a case and statutory approach. Results: The results showed that the Panel of Judges in the case issued a decision different from applicable legal provisions. This indicates that normatively, geothermal mining governance is regulated by Law Number 21 of 2014, while the criminal offense is subject to Law Number 20 of 2001 in conjunction with Law Number 31 of 1999 on the Eradication of Corruption. Conclusion: However, the legal implementation of this decision has been proven to ignore existing regulations and Law enforcement of corruption in the renewable energy sector must prioritize the value of justice in order to protect the community's rights to utilize natural resources. Suggestion: This research suggests strengthening the Judicial Commission oversight and increasing judges capacity to regulate technical matters in the mining sector. Contribution: The results contribute to a jurisprudence-based critical analysis of corruption law enforcement patterns in the green energy sector, while also providing a literature reference for policymakers to minimize legal loopholes in integrating criminal and mining administrative law.